Bridges, not blockades : transcending university politics - Maddox, Gayle; Diede, Martha Kalnin (Critical studies in teacher leadership series, 2020)
More than 3,400 colleges and universities in the United States serve 20.5 million students. While each campus is unique, most campuses and institutions face common issues, including tenure and promotion; budgeting; competition among disciplines for space and funding; academic bullying; and issues of identity. These are just a few of the topics among the many vital areas of concern at schools across the country. In Bridges not Blockades, personal essays related to these cultural and political matters will allow faculty and administrators in higher education to see, hear, and better understand the inner workings of our institutions. Perhaps more importantly, this book demonstrates that faculty and staff at colleges and universities need to embrace our commonalities so that we can meet the challenges of higher education throughout the 21st century. Indeed, some of these essays may suggest ways in which faculty, staff, and administrators have moved from differences to commitment to shared goals to tackle new and existing challenges and opportunities